Isolation and characterization of cellulosenanofibers from Gigantocholoa scortechinii as a reinforcement material - Saurabh, Chaturbhuj Kumar; Mustapha, Asniza; Mohd. Masri, M.; Owolabi, Folahan Abdul Wahab Taiwo; Syakir, Muhammad Izzuddin; Dungani, Rudi; M. Tahir, Paridah; Jawaid, Mohammad; Abdul Khalil, H. P. Shawkataly (Hindawi Publishing Corporation, 2016)
Cellulose nanofibers (CNF) were isolated from Gigantochloa scortechinii bamboo fibers using sulphuric acid hydrolysis. This method was compared with pulping and bleaching process for bamboo fiber. Scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and thermogravimetric analysis were used to determine the properties of CNF. Structural analysis by FT-IR showed that lignin and hemicelluloses were effectively removed from pulp, bleached fibers, and CNF. It was found that CNF exhibited uniform and smooth morphological structures, with fiber diameter ranges from 5 to 10 nm. The percentage of crystallinity was significantly increased from raw fibers to cellulose nanofibers, microfibrillated, along with significant improvement in thermal stability. Further, obtained CNF were used as reinforcement material in epoxy based nanocomposites where tensile strength, flexural strength, and modulus of nanocomposites improved with the addition of CNF loading concentration ranges from 0 to 0.7%.